IMPLEMENTASI KEBIJAKANRETRIBUSI PARKIR BERDASARKAN PERDA NOMOR 4 TAHUN 2011 TENTANG RETRIBUSI UMUM DI KOTA PONTIANAK - NURHAYU, ANISA PRAPTI; Elyta, Elyta; Sujendra, Bima (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
Â The collection technique was through interviews. After that, the collected data were analyzed qualitatively. The writer used the theory of Charles O. Jones (Subarsono, 2006) with 3 variables, namely: 1). Organization, it was concluded that the implementation of policy, operational standards and procedures, financial resources and equipment had been carried out well. 2). Interpretation, it was concluded that the contents and objectives were understood, while dissemination and community support had been carried out by the Transportation Office. 3). Application, it was concluded that the application stage was very important to find out one of the activities in implementing the parking retribution policy, namely the retribution collection on parking had been carried out well but had not reached the maximum target of PAD. Based on the analysis, it was concluded that parking collection was the authority and responsibility of the Pontianak City Transportation Office.Â Keywords: Policy implementation, Parking Retribution.